Critical sets in direct product C3 × Cn of back circulant latin squares - Cao, Haitao; Du, Beiliang (Utilitas Mathematica, 2002)
Stinson and Van Rees have given a construction for critical sets in C2 × Cn for n even. Then, Cooper, Donovan and Gower constructed a family of critical sets in C2 × Cn for n odd. In this paper, we construct some new critical sets in C3 × Cn and show that lcs(n) ≥ (29n2 - 27n)/54 for n ≡ 0 (mod 9).